All-solid-state electrochromic device based on organic conductive polymer
By using cathode and anode layers composed of organic conductive polymers in solid-state electrochromic devices and combining specific electrolyte layers, the problem of long response time of solid-state electrochromic devices is solved, and a short response time and sensitive color discoloration effect is achieved. Electrochromic devices.
Patent Information
- Application Number
- CN202411610314.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-12
- Publication Date
- 2025-02-18
AI Technical Summary
Existing solid-state electrochromic devices have a long response time and are not suitable for use in devices with high requirements for discoloration speed.
All-solid-state electrochromic devices based on organic conductive polymers are adopted, including cathode layer, electrolyte layer and anode layer. The cathode layer and anode layer are composed of p-type and n-type conductive polymer coatings, respectively. The electrolyte layer is composed of electrolytes of specific composition. The slurry is cured.
It realizes the shorter response time and more sensitive color discoloration effect of electrochromic devices, and is suitable for use in devices with high requirements for color discoloration speed.
Smart Images

Figure BDA0005130763490000071 
Figure BDA0005130763490000081 
Figure BDA0005130763490000091
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of electrochromic materials, and more specifically, to an all-solid-state electrochromic device based on organic conductive polymers. Background Art
[0002] The principle of electrochromic (EC) technology is to cause a stable and reversible color change in a material through an applied electric field. This technology can not only achieve dynamic control of external light and solar radiation heat, but also show rich color changes in products such as automobiles, airplanes, glass curtain walls, mobile phones, and smart appliances, greatly improving the functionality of the products.
[0003] To achieve the electrochromic function, traditional electrochromic devices mainly use two types: liquid and solid. For liquid electrochromic devices, liquid electrolytes are usually introduced to change the optical properties of the material. The advantage of this technology is that the reaction speed is fast and rapid color conversion can be achieved, but liquid electrolytes are prone to leakage and bubbles during long-term use. These problems not only affect the optical properties and stability of the device, but also limit its application prospects in portable or mobile application scenarios. In addition, the packaging of liquid devices is more complicated and faces many challenges in large-scale production. Compared with liquid devices, solid-state electrochromic devices solve the above-mentioned problems of leakage and bubble formation by using solid electrolytes instead of liquid electrolytes. However, in actual engineering applications, solid-state devices also have many areas that need to be improved.
[0004] In the related art, there is a solid-state electrochromic device, which is prepared according to the following method: (1) In a glove box, an electrochromic material, hydroxyethyl ferrocene, 1,4-butanediol diacrylate, 2-hydroxyethyl acrylate, a photoinitiator, and bis(trifluoromethylsulfonyl)imide lithium salt are dissolved in vinyl ethylene carbonate and stirred for two hours to obtain a precursor solution; (2) The precursor solution is dropped on a piece of ITO conductive glass, and the edge of the ITO substrate is attached with tape, and then another ITO substrate is offset and covered on it, and the tape is clamped and fixed with a dovetail clip; (3) The prepared uncured device is placed under a UV curing lamp for curing to obtain a single-layer all-solid-state electrochromic device.
[0005] With respect to the above-mentioned related technologies, the inventors believe that although the electrochromic devices in the related technologies have overcome the problem of easy leakage of traditional liquid electrochromic devices, they also have the defect of long response time and are not suitable for use in devices with high requirements for color change speed. Summary of the invention
[0006] In the related art, the electrochromic device has the defect of long response time and is not suitable for use in devices with high requirements for color change speed. In order to improve this defect, the present application provides an all-solid-state electrochromic device based on organic conductive polymer.
[0007] The present application provides an all-solid-state electrochromic device based on an organic conductive polymer, which adopts the following technical scheme: an all-solid-state electrochromic device based on an organic conductive polymer, comprising a cathode layer, an electrolyte layer and an anode layer, wherein the cathode layer comprises a first ITO substrate and a p-type conductive polymer coating, and the anode layer comprises a second ITO substrate and an n-type conductive polymer coating; the components of the n-type conductive polymer coating comprise PBFDO, and the p-type conductive polymer coating comprises EDOT structural units and TPAC6IL-BF4 groups; the electrolyte layer is formed by curing an electrolyte slurry, and the electrolyte slurry comprises the following components: 2-2.5wt% of a lithium salt, 8-8.5wt% of a photoinitiator, and 43-43.5wt% of a cross-linking agent, and the remainder is supplemented to 100% by an organic solvent; the lithium salt comprises LiTFSI, and the cross-linking agent comprises PEGDA gel.
[0008] By adopting the above technical scheme, the present application prepares a p-type conductive polymer coating and an n-type conductive polymer coating on the surface of the first ITO substrate and the second ITO substrate, respectively, and the two conductive polymer coatings are used together as electrochromic materials, and an electrolyte layer is provided. The electrolyte layer ensures the conduction of current between the p-type conductive polymer coating and the n-type conductive polymer coating by virtue of its own good ionic conductivity, and the p-type conductive polymer coating and the n-type conductive polymer coating are used together as electrochromic materials. The present application also defines that the p-type conductive polymer coating contains EDOT structural units and TPAC6IL-BF4 groups, and the synergistic effect of the two can fully reduce the oxidation potential of the polymer and improve the conductivity of the polymer. At the same time, the TPAC6IL-BF4 group can also effectively improve the diffusion and migration ability of ions during the electrochromic process. Therefore, the electrochromic device of the present application has a shorter response time, a more sensitive color change effect, overcomes the defects in the related art, and is suitable for use in equipment with high color change speed requirements.
[0009] Preferably, the components of the p-type conductive polymer coating include a doped conjugated polymer, which is copolymerized by EDOT, coupled modified EDOT and TPAC6IL-BF4, and the coupled modified EDOT is a coupling product of EDOT and a dibrominated aromatic compound.
[0010] By adopting the above technical solution, the present application further defines the component types of the p-type conductive polymer coating and the three types of monomers required for preparing the coating. Among them, the coupling-modified EDOT is a product based on EDOT, in which aromatic groups are introduced through coupling reactions, and it also inherits the polymerizability of EDOT. Through the polymerization of these three types of monomers, an electrochromic device with a shorter response time and more sensitive color change can be obtained.
[0011] Preferably, the coupling-modified EDOT is prepared according to the following method: (1) adding EDOT to THF, stirring and dissolving, cooling with liquid nitrogen, then introducing argon, then adding n-butyl lithium and tributyltin chloride in succession under cooling conditions to react, then placing the system at room temperature and continuing to stir and react, extracting after the reaction is completed, and then drying the organic phase, filtering and rotary evaporating to obtain an intermediate product; (2) Dissolve the dibrominated aromatic compound in DMF, add the intermediate product, and then add bis(triphenylphosphine)palladium dichloride under argon protection to carry out heating reaction. After the reaction is completed, extract the organic phase, dry it, filter and rotary evaporate to obtain a crude product, purify the crude product to obtain coupled modified EDOT.
[0012] By adopting the above technical scheme, the present application limits the substitution reaction of EDOT with tributyltin chloride and EDOT under the action of n-butyl lithium, introduces an intermediate product with a tributyltin group on the aromatic ring, and then reacts the intermediate product with a dibrominated aromatic compound under the catalytic action of bis(triphenylphosphine)palladium dichloride, so that EDOT is grafted to the position where the bromine atom originally existed in the dibrominated aromatic compound, thereby obtaining a coupled modified EDOT.
[0013] Preferably, the dibrominated aromatic compound includes 2,7-dibromo-9,9-spirobifluorene and 4,7-bis(2-bromo-5-thienyl)-2,1,3-benzothiadiazole.
[0014] By adopting the above technical solution, the present application defines the specific types of dibrominated aromatic compounds, and can obtain an electrochromic device with a faster response speed.
[0015] Preferably, the doped conjugated polymer is prepared according to the following method: (1) PSS-Na, EDOT, coupled modified EDOT and TPAC6IL-BF4 are added to water, and a monomer dispersion is obtained after ultrasonic dispersion, which is set aside; an initiator is added to deionized water and dissolved to obtain an initiator solution, which is set aside; (2) adding an initiator solution to the monomer dispersion under heating conditions in a water bath, dialyzing the product after stirring the reaction, and then evaporating and concentrating the remaining liquid after purification, and obtaining a doped conjugated polymer after vacuum filtration.
[0016] By adopting the above technical scheme, the present application uses PSS-Na to assist the dispersion of monomers, and copolymerizes various monomers under the action of an initiator, and finally obtains a doped conjugated polymer containing EDOT structural units and TPAC6IL-BF4 groups and doped with aromatic groups.
[0017] Preferably, in the method for preparing the doped conjugated polymer, the weight ratio of EDOT to coupled modified EDOT is 1:(3-9).
[0018] By adopting the above technical solution, the present application optimizes the weight ratio of EDOT to coupled modified EDOT, and an electrochromic device with a relatively ideal response speed can be prepared within the above range.
[0019] Preferably, in the step (1) of preparing the doped conjugated polymer, tungsten trioxide and EDOT are added into water together.
[0020] By adopting the above technical solution, the addition of tungsten trioxide can further improve the response speed of the electrochromic device, and the polymer can also make up for the defect of low coloring efficiency of tungsten trioxide, thereby obtaining an electrochromic device with more ideal performance.
[0021] Preferably, the amount of tungsten trioxide used is 1.7-2.1 times the weight of EDOT.
[0022] By adopting the above technical solution, the present application optimizes the dosage of tungsten trioxide, which helps to improve the response speed of the electrochromic device.
[0023] Preferably, nano-titanium dioxide is grown on the surfaces of both the first ITO substrate and the second ITO substrate.
[0024] By adopting the above technical solution, the present application stipulates that nano-titanium dioxide is grown on the surface of the first ITO substrate and the second ITO substrate. The introduction of titanium dioxide can increase the adhesion between the polymer and the ITO substrate, and can also provide more electron transmission channels for the electrochromic material, shorten the ion diffusion distance, and help improve the response speed of the electrochromic device.
[0025] Preferably, the nano titanium dioxide is grown according to the following method: (1) Mixing hydrochloric acid and tetrabutyl titanate, and continuing to stir until the solution is clear to obtain a precursor solution for later use; (2) The ITO substrate is cleaned and then placed in a polytetrafluoroethylene liner, a precursor solution is added, and after hydrothermal treatment, it is taken out, washed with deionized water and anhydrous ethanol in turn, and then placed in an oven for drying to complete the growth of nano-titanium dioxide.
[0026] By adopting the above technical scheme, the present application uses tetrabutyl titanate as a titanium source, first acidifies the titanium source, and then realizes the growth of nano-titanium dioxide through a hydrothermal reaction, thereby obtaining a first ITO substrate and a second ITO substrate with nano-titanium dioxide grown on the surface.
[0027] In summary, this application has the following beneficial effects: 1. This application uses an n-type conductive polymer coating containing PBFDO and a p-type conductive polymer coating containing EDOT structural units and TPAC6IL-BF4 groups as electrochromic materials, and achieves a good electrochromic effect with the assistance of an electrolyte layer, thereby obtaining an electrochromic device with a shorter response time and more sensitive color change, which is suitable for use in equipment with higher requirements for color change speed.
[0028] 2. This application defines the component types of the p-type conductive polymer coating and the three types of monomers required to prepare the coating. Among them, the coupling-modified EDOT is a product based on EDOT, with aromatic groups introduced through coupling reactions, and also inherits the polymerizability of EDOT. Through the polymerization of these three types of monomers, an electrochromic device with a shorter response time and more sensitive color change can be obtained.
[0029] 3. In the step of preparing the doped conjugated polymer, tungsten trioxide is added in the present application. The addition of tungsten trioxide can further improve the response speed of the electrochromic device. At the same time, the polymer can also make up for the defect of low coloring efficiency of tungsten trioxide, thereby obtaining an electrochromic device with more ideal performance. DETAILED DESCRIPTION
[0030] The present application is further described in detail below in conjunction with embodiments, preparation examples and comparative examples. The raw materials involved in the present application can all be obtained commercially.
[0031] Preparation example of doped conjugated polymer The following is an explanation using Preparation Example 1.
[0032] Preparation Example 1 In this preparation example, the raw material of the doped conjugated polymer involves a coupling-modified EDOT, which is prepared according to the following method: (1) Add 2 mL of EDOT to 7 mL of dry THF, stir to dissolve, and then cool to 65° C. with liquid nitrogen. Maintain this temperature and introduce argon. Continue cooling for 10 min. Add 1.6 mol of n-butyl lithium. Continue to react for 20 min. Then adjust the temperature to -20° C., cool to -65° C. again after 1 min. Add 6 g of tributyltin chloride after 10 min. After reacting for 5 min, place the system at room temperature at 20° C. and continue to stir and react for 1 h. After the reaction is completed, prepare a solvent according to a volume ratio of dichloroethane: water = 3:1 for extraction. After two consecutive extractions, combine the organic phases, dry the organic phases with anhydrous magnesium sulfate, and then filter and rotary evaporate to obtain an intermediate product. (2) 0.005 mol of a dibrominated aromatic compound (2,7-dibromo-9,9-spirobifluorene is used in this preparation example) is dissolved in 10 mL of DMF, and the intermediate product obtained in step (1) is added. Then, 0.05 g of bis(triphenylphosphine)palladium dichloride is added under argon protection, and the reaction is heated at 90° C. for 2 h. After the reaction is completed, a solvent is prepared according to a volume ratio of dichloroethane: water = 3:1 for extraction. The extraction is repeated twice, and the organic phases are combined. The obtained organic phases are dried using anhydrous magnesium sulfate, filtered and rotary evaporated to obtain a crude product. The crude product is dissolved in dichloroethane, the solvent is removed under reduced pressure, and column chromatography is performed for purification. The eluate is rotary evaporated and dried to obtain a coupled modified EDOT.
[0033] In this preparation example, the doped conjugated polymer was prepared according to the following method: (1) Add 1.2 g of PSS-Na and 300 μL of monomer (composed of TPAC6IL-BF4, EDOT, and coupled modified EDOT in a weight ratio of 5:1:3) to 12 mL of water, stir for 1 hour, and then perform ultrasonic dispersion for 30 minutes to obtain a monomer dispersion for later use; add an initiator (composed of ammonium persulfate and ammonium ferrous sulfate in a weight ratio of 4:1) equivalent to 2% of the weight of the monomer to deionized water and dissolve to obtain an initiator solution for later use; (2) Add the initiator solution to the monomer dispersion under heating conditions at 30°C in a water bath. After 48 hours of stirring reaction, dialyze the product with a 1000Da dialysis bag for 72 hours. Then, evaporate and concentrate the remaining liquid after purification to make the solid content reach 1%. Vacuum filter the liquid using a 2500-mesh nylon filter cloth to obtain a doped conjugated polymer.
[0034] Preparation Example 2 The difference between this preparation example and preparation example 1 is that the dibrominated aromatic compound is 4,7-bis(2-bromo-5-thienyl)-2,1,3-benzothiadiazole.
[0035] Preparation Example 3 The difference between this preparation example and preparation example 2 is that in step (2) of preparing the doped conjugated polymer, the monomers are composed of TPAC6IL-BF4, EDOT, and the coupled modified EDOT of preparation example 2 in a weight ratio of 5:1:6.
[0036] Preparation Example 4 The difference between this preparation example and preparation example 3 is that in step (2) of preparing the doped conjugated polymer, the monomers are composed of TPAC6IL-BF4, EDOT, the coupled modified EDOT of preparation example 1, and the coupled modified EDOT of preparation example 2 in a weight ratio of 5:1:3:6.
[0037] Preparation Example 5 The difference between this preparation example and preparation example 4 is that in step (1) of preparing the doped conjugated polymer, tungsten trioxide with an average particle size of 50 nm and EDOT are added to water together, and the amount of tungsten trioxide used is 1.3 times the weight of EDOT.
[0038] Preparation Example 6 The difference between this preparation example and preparation example 5 is that in step (1) of preparing the doped conjugated polymer, the amount of tungsten trioxide used is 1.7 times the weight of EDOT.
[0039] Preparation Example 7 The difference between this preparation example and preparation example 5 is that in step (1) of preparing the doped conjugated polymer, the amount of tungsten trioxide used is 1.9 times the weight of EDOT.
[0040] Preparation Example 8 The difference between this preparation example and preparation example 5 is that in step (1) of preparing the doped conjugated polymer, the amount of tungsten trioxide used is 2.1 times the weight of EDOT. Example
[0041] Examples 1-5 The following description is given by taking Example 1 as an example.
[0042] Example 1 This embodiment provides an all-solid-state electrochromic device based on an organic conductive polymer, comprising a cathode layer, an electrolyte layer and an anode layer, wherein the cathode layer and the anode layer are respectively arranged on both sides of the electrolyte layer along the thickness direction of the electrolyte layer. The cathode layer comprises a first ITO substrate and a p-type conductive polymer coating with a thickness of 500 nm, and the anode layer comprises a second ITO substrate and an n-type conductive polymer coating with a thickness of 500 μm, and both the n-type conductive polymer coating and the p-type conductive polymer coating are bonded to the electrolyte layer.
[0043] The thickness of the electrolyte layer is 20 μm, and it is formed by curing the electrolyte slurry under ultraviolet light. The electrolyte slurry includes the following components: 2wt% lithium salt, 8wt% photoinitiator, 43wt% crosslinker, and the balance is supplemented to 100% by organic solvent; the lithium salt is LiTFSI, the crosslinker is PEGDA gel, the photoinitiator is initiator 1173, and the organic solvent is propylene carbonate.
[0044] In this embodiment, the electrochromic device is prepared according to the following method: (1) coating the doped conjugated polymer of Preparation Example 1 on the surface of a first ITO substrate, and obtaining a p-type conductive polymer coating after thermal curing, and the two together constitute a cathode layer; coating PBFDO on the surface of a second ITO substrate, and obtaining an n-type conductive polymer coating after thermal curing, and the two together constitute an anode layer; (2) The electrolyte slurry is coated on the surface of the p-type conductive polymer coating, and then the anode layer is covered on the surface of the cathode layer, and the surface of the n-type conductive polymer coating is also in contact with the electrolyte slurry, and then UV curing is performed for 5 minutes to obtain an electrochromic device.
[0045] As shown in Table 1, the differences between Examples 1-5 are mainly in the different raw material ratios of the electrolyte slurry.
[0046] Table 1 Raw material ratio of electrolyte slurry Examples 6-12 As shown in Table 2, the difference between Examples 6-12 and Example 3 is that the preparation examples of the doped conjugated polymers are different.
[0047] Table 2 Preparation examples of doped conjugated polymers sample Preparation Example Example 3 Preparation Example 1 Example 6 Preparation Example 2 Example 7 Preparation Example 3 Example 8 Preparation Example 4 Example 9 Preparation Example 5 Example 10 Preparation Example 6 Embodiment 11 Preparation Example 7 Example 12 Preparation Example 8 Embodiment 13 The difference between this embodiment and embodiment 1 is that nano-titanium dioxide is grown on the surfaces of both the first ITO substrate and the second ITO substrate, and the operation of growing titanium dioxide is performed before coating the doped conjugated polymer and PBFDO.
[0048] Nano-titanium dioxide is grown as follows: (1) Mix 200 mL of 8 wt % hydrochloric acid with 2.5 mL of tetrabutyl titanate, and continue stirring until the solution becomes clear to obtain a precursor solution for later use; (2) Wash the ITO substrate and place it in a polytetrafluoroethylene liner. Add the precursor solution to immerse the side of the ITO substrate to be coated. After hydrothermal treatment at 180°C for 3 hours, take it out and wash it with deionized water and anhydrous ethanol in turn. Then, place it in an oven and dry it for 2 hours to complete the growth of nano-titanium dioxide.
[0049] Embodiment 14 The difference between this embodiment and embodiment 3 is that in the method for preparing the doped conjugated copolymer, the coupled modified EDOT is replaced with the same weight of EDOT.
[0050] Comparative Example Comparative Example 1 This comparative example relates to an electrochromic material, which is prepared according to the following steps: 4,4'-bipyridine (0.5 g, 3.2 mmol) and 5-chloro-1-pentene (0.84 g, 8 mmol) were dissolved in 4 mL of N,N-dimethylformamide, heated to 125°C, stirred and reacted for 48 hours, cooled to room temperature, filtered to obtain a crude product, added acetone and centrifuged repeatedly three times, and the precipitate was vacuum dried to obtain an electrochromic material.
[0051] A solid-state electrochromic device is prepared according to the following method: (1) In a glove box, 50 mg of electrochromic material, 25 mg of hydroxyethyl ferrocene, 181.25 mg of 1,4-butanediol diacrylate, 181.25 mg of 2-hydroxyethyl acrylate, 31.25 mg of photoinitiator 1173, and 93.75 mg of bis(trifluoromethylsulfonyl)imide lithium salt were dissolved in 62.5 mg of vinyl ethylene carbonate, and stirred for two hours to obtain a precursor solution; (2) Drop the precursor solution on a piece of ITO conductive glass, stick it to the edge of the ITO substrate with tape, then cover another ITO substrate on top with a misaligned position, and fix it on the tape with a dovetail clip; the effective color change area is a circle with a radius of 2 cm and an area of 12.5 cm 2 ; (3) The prepared uncured device is placed under a UV curing lamp for curing to obtain a single-layer all-solid-state electrochromic device.
[0052] Comparative Example 2 The difference between this comparative example and Example 3 is that the monomers for preparing the doped conjugated copolymer do not include TPAC6IL-BF4.
[0053] Performance testing methods The response time is used as a test item. The response time refers to the time required for the material to switch between the colored state and the faded state. It is divided into the coloring time and the fading time. The definition adopted in this application is the time required for 90% of the change from a stable optical state to another optical state. The response time of the electrochromic device is measured at 625nm, and the response time of Comparative Example 1 is used as a benchmark to calculate the ratio between the response time of each embodiment and the comparative example and the response time of Comparative Example 1. The result corresponding to the coloring time is recorded as the relative coloring time, and the result corresponding to the fading time is recorded as the relative fading time. Each group is repeated 5 times, and the results are averaged. The results are shown in Table 3.
[0054] Table 3 Relative coloring time and relative fading time Combining Examples 1-5 and Comparative Example 1 and Table 3, it can be seen that the response time measured in Examples 1-5 is shorter than that in Comparative Example 1. This is because the synergistic effect of the EDOT structural unit and the TPAC6IL-BF4 group can fully reduce the oxidation potential of the polymer and improve the electrical conductivity of the polymer. At the same time, the TPAC6IL-BF4 group can also effectively improve the diffusion and migration ability of ions during the electrochromic process, so that the electrochromic devices of Examples 1-5 have a shorter response time and a more sensitive color change effect, which is suitable for use in equipment with higher requirements for color change speed.
[0055] Combining Example 3 and Comparative Example 2 with Table 3, it can be seen that when the TPAC6IL-BF4 group is missing, the synergistic effect of the EDOT structural unit and the TPAC6IL-BF4 group no longer exists, resulting in a slower response speed of the electrochromic device.
[0056] Combining Example 3 and Example 6 with Table 3, it can be seen that the coupled modified EDOT prepared using 2,7-dibromo-9,9-spirobifluorene and 4,7-bis(2-bromo-5-thienyl)-2,1,3-benzothiadiazole can enable the electrochromic device to have a faster response speed.
[0057] It can be seen from Example 3, Examples 6-8 and Table 3 that when the weight ratio of EDOT to coupled modified EDOT is 1:(3-9), the electrochromic device can have a faster response speed.
[0058] It can be seen from Example 8, Example 9 and Table 3 that the addition of tungsten trioxide can further improve the response speed of the electrochromic device, and the polymer can also make up for the defect of low coloring efficiency of tungsten trioxide, thereby obtaining an electrochromic device with more ideal performance.
[0059] It can be seen from Example 9, Examples 10-12 and Table 3 that when the amount of tungsten trioxide used is 1.7-2.1 times the weight of EDOT, the electrochromic device has a faster response speed.
[0060] It can be seen from Example 12 and Example 13 and Table 3 that the response time measured in Example 13 is shorter. This is because the introduction of titanium dioxide can increase the adhesion between the polymer and the ITO substrate, and can also provide more electron transmission channels for the electrochromic material, shortening the ion diffusion distance, which helps to improve the response speed of the electrochromic device.
[0061] It can be seen from Example 3, Example 14 and Table 3 that in the absence of coupled modified EDOT, the response speed of the electrochromic device will decrease to a certain extent.
[0062] The above embodiments are merely explanations of the present application and are not limitations of the present application. After reading this specification, those skilled in the art may make modifications to the embodiments of the present application without any creative contribution as needed. However, as long as they are within the scope of the claims of the present application, they are protected by the patent law.
Claims
1. An all-solid-state electrochromic device based on an organic conductive polymer, characterized in that: The invention comprises a cathode layer, an electrolyte layer and an anode layer, wherein the cathode layer comprises a first ITO substrate and a p-type conductive polymer coating, and the anode layer comprises a second ITO substrate and an n-type conductive polymer coating; the components of the n-type conductive polymer coating comprise PBFDO, and the p-type conductive polymer coating comprises EDOT structural units and TPAC6IL-BF4 groups; the electrolyte layer is formed by curing an electrolyte slurry, and the electrolyte slurry comprises the following components: 2-2.5wt% of a lithium salt, 8-8.5wt% of a photoinitiator, and 43-43.5wt% of a crosslinking agent, and the balance is supplemented to 100% by an organic solvent; the lithium salt comprises LiTFSI, and the crosslinking agent comprises PEGDA gel.
2. The all-solid-state electrochromic device based on organic conductive polymer according to claim 1, characterized in that: The components of the p-type conductive polymer coating include a doped conjugated polymer, which is copolymerized by EDOT, coupled modified EDOT and TPAC6IL-BF4, and the coupled modified EDOT is a coupling product of EDOT and a dibrominated aromatic compound.
3. The all-solid-state electrochromic device based on organic conductive polymer according to claim 2, characterized in that: The coupling-modified EDOT was prepared according to the following method: (1) Add EDOT to THF, stir to dissolve, cool with liquid nitrogen, then introduce argon, then add n-butyl lithium and tributyltin chloride in succession under cooling conditions to react, then place the system at room temperature and continue stirring to react, extract after the reaction is completed, dry the organic phase, filter and rotary evaporate to obtain an intermediate product; (2) Dissolve the dibrominated aromatic compound in DMF, add the intermediate product, and then add bis(triphenylphosphine)palladium dichloride under argon protection to carry out heating reaction. After the reaction is completed, extract the organic phase, dry it, filter and rotary evaporate to obtain a crude product, purify the crude product to obtain coupled modified EDOT.
4. The all-solid-state electrochromic device based on organic conductive polymer according to claim 3, characterized in that: The dibrominated aromatic compounds include 2,7-dibromo-9,9-spirobifluorene and 4,7-bis(2-bromo-5-thienyl)-2,1,3-benzothiadiazole.
5. The all-solid-state electrochromic device based on organic conductive polymer according to claim 2, characterized in that: The doped conjugated polymer is prepared according to the following method: (1) Add PSS-Na, EDOT, coupled modified EDOT and TPAC6IL-BF4 to water, and obtain a monomer dispersion after ultrasonic dispersion, which is set aside; add an initiator to deionized water to dissolve, and obtain an initiator solution, which is set aside; (2) Adding the initiator solution to the monomer dispersion under water bath heating conditions, dialyzing the product after stirring the reaction, and then evaporating and concentrating the remaining liquid after purification, and obtaining the doped conjugated polymer after vacuum filtration.
6. The all-solid-state electrochromic device based on organic conductive polymer according to claim 5, characterized in that: In the method for preparing the doped conjugated polymer, the weight ratio of the used EDOT to the coupled modified EDOT is 1:(3-9).
7. The all-solid-state electrochromic device based on organic conductive polymer according to claim 5, characterized in that: In the step (1) of preparing the doped conjugated polymer, tungsten trioxide and EDOT are added into water.
8. The all-solid-state electrochromic device based on organic conductive polymer according to claim 7, characterized in that: The amount of tungsten trioxide used is 1.7-2.1 times the weight of EDOT.
9. The all-solid-state electrochromic device based on organic conductive polymer according to claim 6, characterized in that: Nano-titanium dioxide grows on the surfaces of the first ITO substrate and the second ITO substrate.
10. The all-solid-state electrochromic device based on organic conductive polymer according to claim 9, characterized in that: The nano titanium dioxide is grown according to the following method: (1) Mix hydrochloric acid and tetrabutyl titanate, and continue stirring until the solution is clear to obtain a precursor solution for later use; (2) The ITO substrate is cleaned and then placed in a polytetrafluoroethylene liner, the precursor solution is added, and after hydrothermal treatment, it is taken out and washed with deionized water and anhydrous ethanol in turn, and then placed in an oven to dry, thereby completing the growth of nano-titanium dioxide.